2020
DOI: 10.1007/s40670-019-00912-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Hidden Curricula: Use of Dark Humor in Anatomy Labs and its Implications for Basic Sciences Education

Abstract: Humor is subjective within most settings, but within the anatomy laboratory, it is likely to be significantly more contentious. While humor may be considered a component of the hidden curriculum of medical education, it has yet to be studied specifically from a basic sciences perspective. This study sought to understand if, when, how, and why humor may be used in anatomy labs and the implications this may have in basic sciences education. A survey consisting of demographic and qualitative items was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…As with patient-provider interactions, the palliative effects of humour at ADC align with findings about humour in other care settings (Rosenberg 1989;Wear et al 2006;Livingston 2012;Issler 2016;Linge-Dahl 2018;Pinna et al 2018;Inêz, José, and Capelas 2018;Dueñas, Kirkness, and Finn 2020). Humour can thus be an important care practice that distracts patients from painful stimuli, consequently lowering the amount of pain they experience during procedures.…”
Section: Patient Comfort and Managing Painsupporting
confidence: 65%
See 1 more Smart Citation
“…As with patient-provider interactions, the palliative effects of humour at ADC align with findings about humour in other care settings (Rosenberg 1989;Wear et al 2006;Livingston 2012;Issler 2016;Linge-Dahl 2018;Pinna et al 2018;Inêz, José, and Capelas 2018;Dueñas, Kirkness, and Finn 2020). Humour can thus be an important care practice that distracts patients from painful stimuli, consequently lowering the amount of pain they experience during procedures.…”
Section: Patient Comfort and Managing Painsupporting
confidence: 65%
“…A further small body of scholarship examines the palliative effects of humour, describing how it increases comfort and decreases pain and can have positive benefits for patients' relatives and medical professionals (Livingston 2012;Linge-Dahl 2018;Pinna et al 2018). Further, humour can function as a coping mechanism among both patients and providers, especially in emotionally fraught circumstances (Inêz, José, and Capelas 2018;Issler 2016;Rosenberg 1989;Dueñas, Kirkness, and Finn 2020;Wear et al 2006).…”
Section: Humour Care and Medicinementioning
confidence: 99%
“…Is the dark humor that helps so many practitioners cope with the nature of the work something that can be shared or, is it at the expense of certain groups and, so, exclusionary? Dueñas et al describe the subjective nature of humor within anatomy, highlighting its use within the anatomy laboratory as subjective and contentious, thus humor becomes a component of the hidden curriculum (Dueñas et al, 2020 ). They study reported the use of an “internal barometer” as a self‐gauge for judgments as to whether jokes or mnemonics where appropriate.…”
Section: Anatomy In the Context Of A Decolonized Or Reimagined Curric...mentioning
confidence: 99%
“…In addition to the initiation of introspection on ethics, empathy, and humanistic values observed in medical students [ 15 19 ], some have reported that dissection-based anatomy teaching can promote respect and compassion [ 20 ]. Furthermore, dissection-based laboratory environments help students to develop coping mechanisms for encounters with and around the topic of death [ 21 ]. These are all crucial elements of the hidden anatomy curriculum that prepare students for a future of patient interactions in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, while knowledge-based assessments can be easily administered via remote examination [ 28 ], evaluation of non-traditional discipline-independent skills that are commonly conveyed via cadaveric dissection (e.g., empathy, compassion, reflection on the topic of death) are difficult to assess and often overlooked. Furthermore, because human anatomy education is traditionally an in-person discipline, published research on how different anatomy teaching formats initiate students’ reflections on ethics and other topics, including reflection on death, are mostly based on traditional approaches that include exposure to a full-body human cadaver or cadaveric specimens [ 6 , 13 , 15 , 16 , 21 , 29 31 ]. There is a paucity of research on whether non-traditional or modified anatomy curricula can elicit similar outcomes as traditional cadaver-based settings, especially during the persistent COVID-19 pandemic [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%